2007
DOI: 10.1007/s12033-007-0001-9
|View full text |Cite
|
Sign up to set email alerts
|

A system for the directed evolution of the insecticidal protein from Bacillus thuringiensis

Abstract: Theoretically, the activity of AB-type toxin molecules such as the insecticidal toxin (Cry toxin) from B. thuringiensis, which have one active site and two binding site, is improved in parallel with the binding affinity to its receptor. In this experiment, we tried to devise a method for the directed evolution of Cry toxins to increase the binding affinity to the insect receptor. Using a commercial T7 phage-display system, we expressed Cry1Aa toxin on the phage surface as fusions with the capsid protein 10B. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 54 publications
0
38
0
Order By: Relevance
“…The level to which rational design of toxins is possible is shown by the engineering of toxicity toward mosquito larvae into the lepidopteran-specific toxin Cry1Aa (Liu and Dean, 2006). Alternatively, a directed evolution system based on phage display technology for producing toxins with improved binding to a receptor, and thus increased toxicity, has been described (Ishikawa et al, 2007).…”
Section: Mutagenesis Of Three-domain Cry Toxinsmentioning
confidence: 99%
“…The level to which rational design of toxins is possible is shown by the engineering of toxicity toward mosquito larvae into the lepidopteran-specific toxin Cry1Aa (Liu and Dean, 2006). Alternatively, a directed evolution system based on phage display technology for producing toxins with improved binding to a receptor, and thus increased toxicity, has been described (Ishikawa et al, 2007).…”
Section: Mutagenesis Of Three-domain Cry Toxinsmentioning
confidence: 99%
“…Using this approach, novel toxins have been generated that exhibit improved activity toward specific insect pests. Previous studies have reported the construction of a library of Cry1Aa toxin Domain II Loop 2 sequences that was displayed on T7 phages and used to evaluate the binding affinity toward the Bombyx mori cadherin receptor [48]. After five rounds of selection, a Cry1Aa mutant containing a mutated Loop 2 in Domain II was obtained that exhibited a 6-fold increase in the insecticidal activity against B. mori , indicating that mutations in this region may affect Cry toxin binding to the receptor [48].…”
Section: Biotechnology Strategies To Speed In Vitro Molecular Evolmentioning
confidence: 99%
“…Directed evolution system based on phage display technology for producing toxins with improved binding to a receptor, and thus increased toxicity, has also been described (Ishikawa et al 2007). …”
Section: Engineering Of Novel Cry Proteinsmentioning
confidence: 99%